Intoxicación natural de avestruces por consumo excesivo de frutos de Samanea saman en Colombia - Hernández-Arroyave, Walter (2020)
A natural intoxication of two specimens of ostrich (Struthio camelus), raised in captivity, as a result of excessive consumption of fruits of saman (Samanea saman) in the Magdalena region of Colombia is presented. The birds had poor body condition, high degree of dehydration, apathy, weakness, drowsiness and subsequently death. The most outstanding macroscopic findings during the necropsy was a severe impaction of the proventriculus due to the accumulation of fruits and seeds of the legume and an extensive area of ​​ulcerated mucosa. The kidney was the organ with the greatest histopathological lesions typical of a nephrotoxic condition. There were no liver lesions. Glutamic oxalacetic (TGO) and glutamic pyruvic (TGP) transaminases were found elevated. Qualitative colorimetric tests revealed the presence of tannins and saponins of the plant material found in proventriculus. The results indicated that the ostriches died due to poisoning due to the consumption of fruits of the saman.